2021
DOI: 10.1007/s10900-021-01004-0
|View full text |Cite
|
Sign up to set email alerts
|

Face Mask Use Among Commercial Drivers During the COVID-19 Pandemic in Accra, Ghana

Abstract: The paper contributes to unravelling the perceptions of urban commercial drivers regarding their vulnerability to catching the SARS-CoV-2 virus while at work. It further examines how the perception of vulnerability influences personal use of face masks by drivers, as well as on their insistence on appropriate masking behaviour by other persons on-board public transport. Overcrowding and unsanitary conditions in informal public transport in Africa could facilitate the spread of the corona virus. However, the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…The similar motive “Maintaining both your and your family members’ health” in our study was chosen by only 53% of responders. The motive “impossible to enter public space” was noted by about the same percentage of respondents in that study as in ours (65% and 66.6%, respectively) [ 7 ]. The motive “Fear of getting fined”, which ranks third in our study (40% of respondents), is also considered by other authors as significant [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The similar motive “Maintaining both your and your family members’ health” in our study was chosen by only 53% of responders. The motive “impossible to enter public space” was noted by about the same percentage of respondents in that study as in ours (65% and 66.6%, respectively) [ 7 ]. The motive “Fear of getting fined”, which ranks third in our study (40% of respondents), is also considered by other authors as significant [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 54%
“…However, in Hanoi, Vietnam, there is a greater adherence of the population to this measure of nonpharmaceutical prevention: 100% of passengers wore face masks, and only 11% wore them incorrectly [ 6 ]. In Ghana, 92.4% of public transport drivers wore masks [ 7 ]. However, there was a low adherence of the passengers to the observance of the “face mask regime” on public transport.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another research result supported this study, finding that the higher the risk perception of COVID-19, the higher level of compliance with COVID-19 prevention behavior [31]- [33]. A study in Ghana also revealed that the more people fear getting COVID-19, their face mask behavior is also consistently high [34].…”
Section: Demographic Status and Risk Infection Related To Mask Compli...supporting
confidence: 61%